OUTCOMES OF MANAGEMENT DEVELOPMENT PROGRAM FOR EMPLOYEES OF NADHLATUL ‘ULAMA HOSPITAL - Ratna Wardani; Dyah Ayu Yulyastuti (The Indonesian Journal of Public Health, 2022)
Introduction: The various management development interventions that have been implemented seem to have not identified the characteristics of the role model, perceived control, and understanding of the Management Development Program (MDP) itself. The MDP effectiveness evaluation model also seems to have not received much attention. Analyze the influence of the characteristics of the Management Development Program, i.e., role models, feelings of control, and understanding that result in organizational commitment, utility, and participatory Behavior. Methods: The research population was 130 employees of NUH Jombang. Samples were taken using a simple random sampling technique of 100 employees from various work units. Statistical analysis used is path analysis to determine the direct and indirect effect on organizational commitment, utility, and participation behavior. Results: The higher MDP characteristics that consist of role model, perceived control, and understanding will be followed by high organizational commitment, utility, and participative behavior as positive outcomes. Conclusion: The study results can improve understanding of the characteristics of the relevant Management Development Program to improve employee outcomes. Employee outcome, i.e., organizational commitment, Utilities which include intrinsic – extrinsic – organizational benefits, behavior that includes the willingness to participate in development activities, innovative behavior that is beneficial to the organization, and sharing opinions.